FDI IN MULTI-BRAND RETAIL IN INDIA: MYTHS AND REALITIES - B. R. Kundgir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Foreign Direct Investment (FDI) in India’s retail sector has been a topic of debate for years. This paper examines the policy changes allowing FDI in multi-brand retail, its potential benefits, and common myths. Using secondary data from books, journals, government documents, and recent reports, we analyze trends in the Indian retail market, government policies, and the impact on the economy. Despite allowing 51% FDI in multi-brand retail since 2012, actual inflows have been low due to strict conditions. However, FDI has helped improve supply chains and create jobs in related areas. The paper concludes that with proper regulations, FDI can boost growth without harming small retailers.